The Integration of Technology in Family Christian Religious Education in the Digital Era - Buaya, Desrin Wati; Kolibu, Dirk R. (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2024)
In the digital era, the influence of technology is increasingly pervasive in family life, posing new challenges for Christian religious education. This article examines the dynamics of integrating technology into the model of family Christian religious education as a response to the changing times. Families, as the center of shaping Christian values and faith, face significant challenges and disruptions due to technological advancements. The problem-solving approach advocated in this article promotes the integration of technology as a means to deepen understanding and experience of Christian faith within the family environment. Focusing on relevant learning models in the digital age, this research explores how technology can be utilized to uphold Christian religious values and enhance family participation in the religious education process. Previous studies have highlighted the benefits of technology in education, but this research specifically emphasizes the potential integration of technology in family Christian religious education. Literature analysis supports the idea that technology can offer solutions to overcome challenges in delivering Christian religious teachings amidst rapid technological advancements. By addressing literature gaps, this research offers concrete solutions to reconcile the dilemma between religious tradition and digital trends. Additionally, it provides practical guidance for parents, educators, and policymakers to wisely utilize technology in supporting family Christian religious education in the digital age. In conclusion, this article sets the stage for a deeper and more relevant understanding of Christian faith within the family context in the modern technological era within the given word limit.